Structural Elucidation of Phytoconstituents (Phenols, Long Chain Fatty Acids, Flavonoid, Terpenoids, Coumarin) Found in Chromolaena odorata through Gas Chromatography: Mass Spectroscopy (GC-MS) Technique - Pawar, Manjushree Kundalik; Dwivedi, Jayesh Ashok; Dwivedi, Udichi Kataria (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Chromolaena odorata (CO) is a well-known ethnopharmacological herb in Ayurveda and exhibits a comprehensive range of therapeutic potential. Objectives The objective of this research was to study the phytochemical profile of ethanolic extract of CO by Gas Chromatography Mass Chromatography (GC-MS) analysis. Materials and Methods Ethanolic extract of CO was prepared by soxhlet extraction and the extract was subjected to GC-MS analysis (Agilent 7890A GC System) for chemical characterization of the extract. The constituents were analysed by matching the mass spectra with MS libraries. Results and Conclusion Total 24 compounds were identified in the extract and the constituents belonging to various chemical classes like phenols, coumarin, terpenoids, Long Chain Fatty Acids (LCFA) and flavonoid were identified. Compounds include phenol,4-ethenyl-acetate; 2-methoxy-4-vinyl phenol; 2H-1-Benzopyran-2-one,3,4-dihydro; 2-propenoic acid,3-(2-hydroxy phenyl); 1H-cyclopenta [1,3] cyclopropa [1,2] benzene, octahydro-7-methyl-3-methyene-4-(1-methylethyl)-(3As-(3aα,3bβ,7α,7aS*]; trans-z- -bisabolene epoxide; 1H-Inden-1-one,7-(1,1-dimethylethyl)-2,3-dihydro-3,3-dimethyl; 2-pentadecanone 6,10,14-trimethyl; hexadecanoic acid, methyl ester; hexadecanoic acid, ethyl ester; 9,12,15-octadecatrienoic acid; phytol; oleic acid; 2H-Pyran,2-(7-heptadecynyloxy) tetrahydro; squalene etc. The presence of these phytoconstituents could be of potential use of this plant and would help researchers to work with different in vivo and in vitro models.
Keywords: Chromolaena odorata; Phytoconstituents; Phenol; Flavonoid; Terpenoids; LCFA